2012
DOI: 10.4149/gpb_2011_04_364
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent ultrastructural changes of coronary artery in spontaneously hypertensive rats

Abstract: The age-dependent differences in basic cardiovascular parameters, geometry and structure of coronary arteries between Wistar and spontaneously hypertensive rats (SHR) were evaluated. SHR of the age 3-, 9-, 17-, and 52-week and age-matched Wistar rats were used. Blood pressure (BP) was measured by the plethysmographic method. Animals were perfused with a glutaraldehyde fixative under pressure of 90 mmHg (3-week-old) and 120 mmHg (9-, 17-, 52-week-old). Coronary arteries were processed for electron microscopy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…This study investigates the effect of subchronic treatment with Epi in young SHR rats, at the peripubertal age, which is a critical developmental period when BP increases rapidly in SHR [39, 40]. We show that continuous Epi treatment during this period significantly prevented BP increase and reduced spontaneous locomotor hyperactivity in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigates the effect of subchronic treatment with Epi in young SHR rats, at the peripubertal age, which is a critical developmental period when BP increases rapidly in SHR [39, 40]. We show that continuous Epi treatment during this period significantly prevented BP increase and reduced spontaneous locomotor hyperactivity in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…A later study of Boulesteix et al (Boulesteix et al, 2006) found that murine coronary arteries do not contain many elastin laminae as found in aorta and carotid arteries. It was reported that the volume density of SMC was 74% while that of extracellular matrix (i.e., collagen and elastin fibers, ECM) was 17% for adult murine coronary media (Cebova and Kristek, 2011). The ratio of collagen to elastin content was 3.7 in media layer of porcine RCA (Garcia and Kassab, 2009) which was slightly larger than that of intact coronary arteries (e.g., ratio of intact canine coronary arteries was reported as 3.1 by Fischer and Llaurado, 1966) likely due to the lower ratio of collagen to elastin in adventitia.…”
Section: Morphology and Mechanics Of Coronary Arteriesmentioning
confidence: 99%
“…Although much efforts have been made to quantify structural change of aorta with age (Tsamis et al, 2013), quantitative data of coronary arteries is limited (Cebova and Kristek, 2011; Ozolanta et al, 1998). Ozolanta examined structural and mechanical properties of 205 human coronary arteries (Ozolanta et al, 1998).…”
Section: Structural Evolutions and Mechanical Changes In Aged And Dmentioning
confidence: 99%
See 2 more Smart Citations